Pengaruh Influencer Marketing, Live Streaming Dan Customer Review Terhadap Purchase Decision Pada Platform TikTok Shop Di Kota Malang - Yudiarosa, Melinda; Farida, Eka; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of influencer marketing, live streaming, and customer reviews on purchase decisions on the TikTok shop platform in Malang City. The research method used is a quantitative approach with a population consisting of consumers who have made transactions on TikTok Shop in Malang City. Data processing was carried out using multiple linear regression analysis with the help of SPSS software. The results show that influencer marketing, live streaming, and customer reviews have a significant influence on purchase decisions, both simultaneously and partially. Influencer marketing is proven to play a role in promoting products through attractive and creative content, reaching a wide audience, building trust, and encouraging consumers to make purchases on TikTok shop. Live streaming is also proven effective, where direct information delivery through product explanations and real-time interactions helps consumers better understand the products and strengthens their confidence in making purchase decisions. In addition, positive customer reviews can enhance potential buyers' trust by providing a real depiction of product quality, thereby encouraging purchase decisions on TikTok shop.  Keywords: Influencer Marketing, Live Streaming, Customer Review, Purchase Decision